The pace of development of internal and external trade of the EAEU (Journal of Philosophy Culture and Political Science, 2018)
The creation and functioning of the Eurasian Economic Union (EAEU) is taking place in the conditions of the world economic crisis. Despite this, the internal and external trade of the EAEU over the past year shows a dynamic growth. The purpose of the research work is to analyze the development of the internal and external trade of the EAEU.Scientific and practical significance of the work – functioning of the EAEU contributes to the diversified development of Europe and Asia, overcoming the global economic crisis. And also, it gives a new impetus to the joint development of post-Soviet countries. The theoretical and practical significance of the political study of these problems is beyond doubt. The research methodology is based on system, comparative, content and event analyzes.Results and results of the study: problems and peculiarities of internal and external trade of the EAEU have been studied, scientific results will help to develop integration within the framework of the EAEU.The value of the research – contributes to the development of integration processes on the expanses of Eurasia.Key words: Eurasian Economic Union – EAEU, internal and external trade, integration.